Baski : Step Grafik Matbaacilik. - Galeri Nev, Istanbul (Istanbul : Galeri Nev, 2009)
Borlakov, Bashir ; Tolon, Canan ; Gül, Deniz ; Alpay, Elvan ; Aksel, Erdäg ; Tenger, Hale ; Eviner, Inci ; Mazici, Melek ; Berg, Mike ; Morova, Murat ; Topçuoglu, Nazif ; Er, Nermin ; Arat, Serdar ; Erdogmus, Tayfun
Baski / Print : Step Grafik Matbaacilik, Galeri Nev, Istanbul, April 2009
boek
Keywords: Turkije